Cutting through spiritual materialism - Trungpa, Chogyam (Boston : Shambhala South Asia Editions, 2012)
walking the spiritual path properly is a very subtle process; it is not something to jump into naively. There are numerous sidetracks which lead to a distorted, ego-centered version of spirituality; we can deceive ourselves into thinking we are developing spiritually when instead we are strengthing our egocentricity through spiritual techniques. This fundamental distortion may be I referred to as spiritual materialism. ' The now classic Cutting Through Spiritual Materialism is the record of two series of lectures given by Trungpa Rinpoche in 1970-71. 'First discussed are the various ways in which people involve themselves in spiritual materialism, the many forms of self deception into which aspirants may fall. After this tour of the sidetracks along the way, the broad outlines of the true spiritual path are discussed. The approach presented is a classical Buddhist one-not in a formal sense, but in the sense of presenting the heart of the Buddhist approach to spirituality. Although the Buddhist way is not theistic, it does not contradict the theistic disciplines, Rather the differences between the ways are a matter of emphasis and method. The basic problems of spiritual materialism are common to all spiritual disciplines.' Chogyam Trungpa-meditation master, scholar, and artist-was well-known throughout the United States, Canada, and Europe as a Buddhist teacher and founder and president of Vajradhatu, Naropa Institute, and Shambhala Training. Former abbot of the Surmang monasteries, he is also the author of The Myth of Freedom, Meditation in Action, and Shambhala: The Sacred Path of the Warrior. (all published by Shambhala).
Includes index.
Keywords: Spiritual life -- Buddhism